Deconstruction Of Content As Prevention Of Terrorism: Social Media Study Of The National Agency For Counterterrorism (BNPT) - Febrityas Febrityas; Muhammad Syauqillah (Cakrawala Repositori IMWI, 2023)
The role of government and society in social media is urgently needed as a counter-narratives of propaganda from terrorist group to against the spread of narratives of hoax, intolerance, extremism and radicalism. However, there is still a bias in building narratives against terrorist groups. It is necessary to carry out deconstruction efforts to prevent terrorism through the media. This study uses a virtual ethnographic approach to see how far the construction of counter-narratives, counter-propaganda is made by the government, so we can see things that need to be deconstructed. The results of the study show that in some BNPT social media, the counter-narrative content towards radical groups is more dominant, so it is giving rise to stigma, secondary deviation, and the difficulty of understanding the diction that appears in a counter-narrative content by the society. So that later it can be classified what can be consumed by the public and not. The public wants practical and instant content, short videos, and information that can be understood by all people.